Family Health Literacy Strengthening through Kader Surabaya Hebat Mentoring Strategies - Ismaicha Dewanti Ramadhania; Monica Widyaswari (Journal of Nonformal Education, 2026)
Background – Family health literacy encompasses the ability to access, understand, evaluate, and use health information for decision-making. Research Urgency – Families increasingly face complex health information and require contextual assistance that helps translate information into appropriate decisions and actions. Research Objectives – This study analyzes the mentoring strategies used by Kader Surabaya Hebat to strengthen family health literacy and identifies supporting and inhibiting factors in Simomulyo, Surabaya. Research Method – A qualitative case study involved Kader Surabaya Hebat members, assisted families, a cadre coordinator, and community health center staff. Data were collected through in-depth interviews, observation, and documentation and analyzed using an interactive model; validity was ensured through source and technique triangulation. Research Findings – Mentoring was implemented adaptively through needs identification, personal communication, information simplification and clarification, monitoring, follow-up, and service facilitation. Implementation was supported by family openness, cadre experience and rapport, inter-cadre coordination, and institutional support, while administrative burden, time constraints, varied family capacities and responses, and inconsistent follow-up were obstacles. Research Conclusion – Strengthening family health literacy requires contextual, dialogic, and sustainable mentoring rather than one-way information dissemination. Research Novelty/Contribution – The study frames Kader Surabaya Hebat mentoring as health-literacy mediation and non-formal family learning.